Restitution for Child Victims as a Recovery Instrument: A Jurisprudential Analysis of Judicial Considerations in Criminal Cases - Vuzio Fernanda; Hafrida Hafrida; Sahuri Lasmadi (Jurnal Jurisprudence, 2025)
ABSTRACT Purpose of the Study: This study aims to examine the construction of judicial reasoning across three levels of s, as well as identify the points which indicate disharmony between the principle of legality, the criminal justice regime, child protection norms, and state finance regulations that contribute to divergent legal reasoning among the District Court, High Court, and Supreme Court decisions. The paper aims to discover why the authority to grant restitution is not exercised in a uniform manner and the extent to which regulatory gaps affect the justice system’s ability to guarantee effective victim recovery. Methodology: This study employed a normative juridical research method . Primary legal materials included Government Regulation No. 43 of 2017, the Child Protection Law, the Law on the Witness and Victim Protection Agency, the State Financial Law, and international instruments on victims’ rights. The jurisprudential analysis focused on Supreme Court Decision No. 5642 K/Pid.Sus/2022 by examining the legal reasoning at each judicial level to map consistency, deviations, and normative conflicts. The conceptual approach was used to interpret the principle of legality, theories of authority, individual offender liability, and victim recovery principles. Results: The findings show that the District Court’s order requiring the Ministry of Women’s Empowerment and Child Protection to pay restitution was driven by a victim-oriented recovery approach but conflicted with the principle of legality and exceeded judicial authority. The High Court corrected this by returning the responsibility to the offender, and the Supreme Court reaffirmed this position based on personal liability and adherence to the state finance regime. The Supreme Court emphasized that judges cannot assign restitution obligations to the state without a clear legislative basis. The study further confirms a critical legal vacuum: no substitution mechanism exists when offenders are unable to pay, resulting in incomplete realization of victims’ rights despite a comprehensive assessment of losses. The lack of synchronization between child protection regulations, criminal law, and state finance governance constitutes a major barrier to effective restitution. Applications of this Study: This research’s findings can serve as a foundation for improving restitution regulations, particularly the need to establish a recovery scheme enabling the state to act lawfully when offenders are unable to pay. The analysis also provides guidance for judges and policymakers on the limits of judicial authority and the importance of harmonizing child protection, criminal law, and state financial regulations in shaping victim-recovery policies. Novelty/Originality of this study: The originality of this study lies in its critical mapping of the relationship between judicial reasoning, limits of authority, and normative conflicts in child-victim restitution cases, an area that is not yet fully elaborated in existing literature. This analysis explicitly reveals the regulatory vacuum that produces divergent reasoning among courts and underscores the need for normative reconstruction, so that restitution mechanisms can operate effectively without violating the legality principle. Keywords: Child; Judicial Considerations; Restitution.   ABSTRAK  Tujuan : Studi ini bertujuan untuk meneliti konstruksi penalaran yudisial di tiga tingkatan pengadilan dalam Kasus No. 5642 K/Pid.Sus/2022 mengenai penentuan restitusi bagi korban anak dalam tindak pidana, serta mengidentifikasi poin-poin yang menunjukkan ketidakselarasan antara prinsip legalitas, rezim peradilan pidana, norma perlindungan anak, dan peraturan keuangan negara yang berkontribusi pada perbedaan penalaran hukum di antara putusan Pengadilan Negeri, Pengadilan Tinggi, dan Mahkamah Agung. Makalah ini bertujuan untuk menemukan mengapa kewenangan untuk memberikan restitusi tidak dilaksanakan secara seragam dan sejauh mana kesenjangan regulasi memengaruhi kemampuan sistem peradilan untuk menjamin pemulihan korban yang efektif. Metodologi: Studi ini menggunakan metode penelitian yuridis normatif dengan menggunakan pendekatan yurisprudensi, pendekatan kasus, dan pendekatan konseptual. Materi hukum primer meliputi Peraturan Pemerintah No. 43 Tahun 2017, Undang-Undang Perlindungan Anak, Undang-Undang tentang Lembaga Perlindungan Saksi dan Korban, Undang-Undang Keuangan Negara, dan instrumen internasional tentang hak-hak korban. Analisis yurisprudensi difokuskan pada Putusan Mahkamah Agung No. 5642 K/Pid.Sus/2022 dengan memeriksa penalaran hukum di setiap tingkat peradilan untuk memetakan konsistensi, penyimpangan, dan konflik normatif. Pendekatan konseptual digunakan untuk menafsirkan prinsip legalitas, teori otoritas, tanggung jawab pelaku individu, dan prinsip pemulihan korban. Hasil: Temuan menunjukkan bahwa perintah Pengadilan Negeri yang mewajibkan Kementerian Pemberdayaan Perempuan dan Perlindungan Anak untuk membayar restitusi didorong oleh pendekatan pemulihan yang berorientasi pada korban tetapi bertentangan dengan prinsip legalitas dan melampaui wewenang peradilan. Pengadilan Tinggi mengoreksi hal ini dengan mengembalikan tanggung jawab kepada pelaku, dan Mahkamah Agung menegaskan kembali posisi ini berdasarkan tanggung jawab pribadi dan kepatuhan terhadap rezim keuangan negara. Mahkamah Agung menekankan bahwa hakim tidak dapat membebankan kewajiban restitusi kepada negara tanpa dasar legislatif yang jelas. Studi ini lebih lanjut menegaskan adanya kekosongan hukum yang kritis: tidak ada mekanisme substitusi ketika pelaku tidak mampu membayar, sehingga mengakibatkan realisasi hak-hak korban yang tidak lengkap meskipun telah dilakukan penilaian kerugian yang komprehensif. Kurangnya sinkronisasi antara peraturan perlindungan anak, hukum pidana, dan tata kelola keuangan negara merupakan hambatan utama bagi restitusi yang efektif. Aplikasi Studi Ini: Temuan penelitian ini dapat menjadi dasar untuk meningkatkan peraturan restitusi, khususnya kebutuhan untuk menetapkan skema pemulihan yang memungkinkan negara untuk bertindak secara sah ketika pelaku tidak mampu membayar. Analisis ini juga memberikan panduan bagi hakim dan pembuat kebijakan tentang batasan kewenangan yudisial dan pentingnya harmonisasi perlindungan anak, hukum pidana, dan peraturan keuangan negara dalam membentuk kebijakan pemulihan korban. Kebaruan/Orisinalitas Studi: Orisinalitas studi ini terletak pada pemetaan kritisnya terhadap hubungan antara penalaran yudisial, batasan kewenangan, dan konflik normatif dalam kasus restitusi anak korban, suatu bidang yang belum sepenuhnya diuraikan dalam literatur yang ada. Analisis ini secara eksplisit mengungkapkan kekosongan regulasi yang menghasilkan penalaran yang berbeda di antara pengadilan dan menggarisbawahi perlunya rekonstruksi normatif, sehingga mekanisme restitusi dapat beroperasi secara efektif tanpa melanggar prinsip legalitas.  Kata Kunci: Anak; Pertimbangan Yudisial; Restitusi